Leitura e leitores no Brasil, 1820-1822: o esboço frustrado de uma esfera pública de poder - Neves, Lúcia Maria Bastos P. (Acervo, 2012)
In the Luzo-Brazilian world, the Constitutional movement of 1821 unleashed an intense debate upon the ideas proposed by liberalism. Printing - of political tracts and papers - held a fundamental role in this slight widening of the sphere of power beyond the narrow circles of the Court. Government, however, remained addicted to the practices inherited from the Ancien Régime. In fact, it was unable to transform the printed word into a tool, with which to draw public opinion on its side.